Evaluation of Skin Permeation and Analgesic Activity Effects of Carbopol Lornoxicam Topical Gels Containing Penetration Enhancer - Saleh A. Al-Suwayeh; Ehab I. Taha; Fahad M. Al-Qahtani; Mahrous O. Ahmed; Mohamed M. Badran (The Scientific World Journal)
The current study was designed to develop a topical gel formulation for improved skin penetration of lornoxicam (LOR) for enhancement of its analgesic activity. Moreover, the effect of different penetration enhancers on LOR was studied. The LOR gel formulations were prepared by using hydroxylpropyl methylcellulose (HPMC) and carbopol. The carbopol gels in presence of propylene glycol (PG) and ethanol were developed. The formulated gels were characterized for pH, viscosity, and LOR release using Franz diffusion cells. Also, in vitro skin permeation of LOR was conducted. The effect of hydroxypropyl β-cyclodextrin (HP β-CD), beta-cyclodextrin (β-CD), Tween 80, and oleic acid on LOR permeation was evaluated. The optimized LOR gel formulation (LORF8) showed the highest flux (14.31 μg/cm2/h) with ER of 18.34 when compared to LORF3. Incorporation of PG and HP β-CD in gel formulation (LORF8) enhanced the permeation of LOR significantly. It was observed that LORF3 and LORF8 show similar analgesic activity compared to marketed LOR injection (Xefo). This work shows that LOR can be formulated into carbopol gel in presence of PG and HP β-CD and may be promising in enhancing permeation.